Tournament planning proposal for a junior player - Penalva, F. J. (Coaching and Sport Science Review, 2018)
This article proposes a season tournament calendar for a 16 year old player with a good tennis level, prioritizes the different training periods, and matches tournaments to the player´s level of play. It also puts an emphasis on geographical proximity.